Bioprospecção alvo-direcionada de moduladores da família das proteínas inibidoras de apoptose (IAPS) em extratos de microrganismos marinhos - Barbosa, Gabriel Henrique [UNIFESP] (2018)
Introduction: Electing a good molecular target is still a hindrance regarding the discovery of new drugs. The Inhibitor of Apoptosis Protein family (IAPs) is a relevant target in cancer research, as we find members of this class overexpressed in several tumor types and almost totally absent in normal cells. Objective: Thus, this work aimed to prospect, through a target-guided approach, natural products produced by marine actinobacteria that act as modulators of the IAP family, validating its activity and interaction through in vitro assay. Methods: Three members of the IAP family (i.e. survivin, livin and XIAP) obtained by heterologous expression in E. coli vector were attached to a resin support and incubated with marine actinobacteria extracts using a bioaffinity assay called functional chromatography. Molecules retained in the resin were eluted and analyzed by HPLC-MS, resulting directly in the mass of the ligand. We fractionated the crude extract of the selected actinobacteria (BRA-214) in Sephadex-LH20, silica cartridge, semi-preparative HPLC and manually collected in analytical HPLC, monitored by DAD detector. Isolated compounds were tested for their IC50 in SK-MEL-19 cells and, by Western blotting, inquired about their effects on protein expression of the IAP survivin and other relevant apoptosis markers. Results: 19 crude extracts were submitted to bioaffinity assays; two of them resulted in hits. The selected extract, produced by actinobacteria BRA-214, previously identified as a member of the Streptomyces genus, returned hits of m/z 613, 670, 684, 704, 718 and 752 (M+H+]. Four of them (m/z 613, 704, 718 and 752) were successfully isolated and seem to be unpublished structures. Their fragmentation profile indicates that they belong to the same class of non-ribosomal peptides, except for the 613 m/z hit, which seems to be from another unknown class. The treatment with the compound of m/z 704 promoted a lower expression of survivin in SK-MEL-19 cells. Conclusion: Functional chromatography showed to be a valid and applicable technique to bioprospect ligands to protein from the IAP family, allowing the identification and recovery of unprecedented secondary metabolites that seem to interact and modulate this family of proteins.